The ART of performance: engaging young people with assisted reproductive technologies*. Issue 2 (3rd April 2019) - Jadva, Vasanti; Vilsbol, Tatiana; Ayed, Nadia; Imrie, Susan; Jones, Catherine M.; Lamba, Nishtha; McConnachie, Anja; Vasques, Simone; Golombok, Susan; Zadeh, Sophie
ABSTRACT: More children than ever before are conceived with the use of assisted reproductive technologies and many are raised in families that are structurally different from most. Research on the experiences of children growing up in diverse families has shown that children may face disapproval, a lack of understanding, and in some cases, bullying by those outside of their home environment, including from their peers at school This study evaluated the use of theatrical performance and post-performance discussions as a method of informing young people about different families. Findings indicated that performance was an effective and engaging learning tool, as it presented first-hand experiences of family diversity. Post-performance discussions were important in enabling young people to improve their understanding of different methods of Assisted Reproductive Technologies and diverse family forms. Young people were found to value engagement activities that are unbiased, interactive, and do not make them feel awkward or uncomfortable.